Gaze behaviours in infancy: Rethinking their development as a dynamic system. (2nd January 2017) - Mathew, Mili; Rajanna, Manjula
Abstract: Purpose : Eye gaze is an important element of communication and serves as an index of deficits in atypically developing children. This study examined the development of gaze behaviours in typically-developing infants within the Dynamic Systems framework which stresses variability and nesting in the development of any behaviour. Method : Nine infants (six males and three females) were videotaped during play/interactions with their primary caregiver between the ages of 3–12 months. The video samples were coded for the occurrence of six gaze behaviours. The rates of occurrence of these behaviours were calculated and non-linear methods were used to analyse the data. Result : The growth trajectories of three behaviours revealed non-linear and linear patterns and environment exploration-related behaviours demonstrated an age at which reliable change in the rate of occurrence was seen within the developmental period. Further, correlations in the occurrence of few behaviours indicated that the gaze system exhibits nested growth. Conclusion : These results suggest, with caution, that development in the gaze system is dynamic in nature. Thus, development should not only be viewed as skills achieved by an expected age due to biological maturation, but also as variable skills whose occurrence is dependent on factors such as environmental and parental influences.